PENDIDIKAN PEREMPUAN: Kajian Sejarah yang Terabaikan - Samsul Nizar (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2008)
In historical study, the woman character constitutes ignoring study. Whereas, the existence of woman always is discussed in some events and some fields, without exception of educational study, even in the classical period until nowadays. But, the woman is merely considered as explanation object. It means it often appears in thought discourse is the women as object thought not as subject thought itself. Therefore, it is worth opening books or scriptures, so that, their indexes are filled with men’s names, moreover, the women’s names are only mentioned if the study talks about woman history. Even though, it does not mean that, there is not woman character appearing and mastering knowledge in some fields. The fields that get attention from woman character namely; Islamic law, poem, and mysticism.